Neuronal ferroptosis after intracerebral hemorrhage - Ren, Siying; Chen, Yue; Wang, Likun; Wu, Guofeng (Frontiers in Molecular Biosciences, 2022)
Intracerebral hemorrhage (ICH) is a devastating form of stroke with high rates of morbidity, mortality, and disability. It induces cell death that is responsible for the secondary brain injury (SBI). The underlying mechanism of SBI after ICH is still unclear, and whether it is related to iron overload is worthy to be discussed. Ferroptosis is an iron-dependent non-apoptotic modes of cell death and plays a particularly important role in the occurrence and progression of ICH. Many ICH-induced regulators and signalling pathways of ferroptosis have been reported as promising targets for treating ICH. In this article, we review the definition, characteristics, and inhibition methods of neuronal ferroptosis caused by iron deposition after ICH, and review the biomarkers for ferroptosis.